EVALUASI PENERAPAN REKAM MEDIS ELEKTRONIK PADA FASILITAS PELAYANAN KESEHATAN DI INDONESIA: A SYSTEMATIC REVIEW - Rahayu, Eka Putri; Ariyanti, Rea (Journal of Health Service Management, 2025)
Background: The issuance of the Minister of Health Regulation Number 24 of 2022 requires every health care facility to improve the medical record management system that has not been implemented optimally. Every health care facility, including hospitals, is required to implement an electronic patient medical history recording system no later than December 2023. With the implementation deadline ending at the end of 2023, many health care facilities are immediately complying with the regulation, although in reality not all health care facilities have been able to implement Electronic Medical Records according to its standards. Objectives: This study aims to evaluate the implementation of electronic medical records in health care facilities in Indonesia. Methods: This study is a systematic review compiled based on the PRISMA flowchart method as a guide. Three electronic databases used in the literature search are: Portal Garuda, Pubmed and Science Direct. Boolean "AND" and "OR" are used to combine keywords described in Table 1. Articles are selected based on the last 3 years of publication, namely from 2022-2024. Results: From the 6 literature findings, the evaluation related to the application of electronic medical records used was the TAM (Technology Acceptance Model) method to assess technology acceptance from three main aspects, namely perceived usefulness, perceived ease of use, and interest in using (behavioral intention to use). These 6 pieces of literature discuss 3 main aspects of the TAM method Conclusion: The implementation of electronic medical records in hospitals has great potential to improve the efficiency and quality of health services. However, successful implementation is highly dependent on comprehensive handling of various aspects, especially human resources, infrastructure and regulations.